Mindfulness and Contemplation: Secular and Religious Traditions in Western Context. Issue 1 (April 2015) - Stratton, Stephen P.
<x xml:space="preserve">Abstract</x> This article considers the growth of mindfulness as a secular practice embedded in a culture that is pluralistic but still primed by Western religion and spirituality. Eastern and Western meditational practices are compared and contrasted for greater understanding of the strengths of each. Western contemplative practices are described as an attentional training process with common factors related to mindfulness. Even as Eastern and Western meditational forms are distinguished, the shared concerns of those who value a religious–spiritual perspective in counseling are raised. Ethical implications are discussed related to informed consent, competence, and multicultural awareness.